A Resin‐Supported Formate Catalyst for the Transformative Reduction of Carbon Dioxide with Hydrosilanes. Issue 35 (2nd June 2020) - Pramudita, Ria Ayu; Manaka, Yuichi; Motokura, Ken
Abstract: A heterogeneous formate anion catalyst for the transformative reduction of carbon dioxide (CO2 ) based on a polystyrene and divinylbenzene copolymer modified with alkylammonium formate was prepared from a widely available anion exchange resin. The catalyst preparation was easy and the characterization was carried out by using elemental analysis, Fourier transform infrared (FTIR) spectroscopy, X‐ray photoelectron spectroscopy (XPS), and solid‐state 13 C cross‐polarization/magic‐angle spinning nuclear magnetic resonance ( 13 C CP/MAS NMR) spectroscopy. The catalyst displayed good catalytic activity for the direct reduction of CO2 with hydrosilanes, tunably yielding silylformate or methoxysilane products depending on the hydrosilanes used. The catalyst was also active for the reductive insertion of CO2 into both primary and secondary amines. The catalytic activity of the resin‐supported formate can be predicted from the FTIR spectra of the catalyst, probably because of the difference in the ionic interaction strength between the supported alkylammonium cations and formate anions. The ion pair density is thought to influence the catalytic activity, as shown by the elemental and solid‐state 13 C NMR analyses. Abstract : A C1 synthon : A heterogeneous formate anion catalyst for CO2 reduction was successfully prepared from anion exchange resin, and it was characterized by FTIR, XPS, and solid‐state 13 C CP/MAS NMR spectroscopy measurements. The catalyst was active both for direct reductive hydrosilylation of CO2 and reductive insertion of CO2 into amines and easily recyclable. Furthermore, a metric to predict the activity of various formate catalysts for CO2 hydrosilylation was also obtained.